Performance analysis of Aquifer Thermal Energy Storage (ATES). (February 2020) - Fleuchaus, Paul; Schüppler, Simon; Godschalk, Bas; Bakema, Guido; Blum, Philipp
Abstract: The objective of the current study is to assess the technical performance of Aquifer Thermal Energy Storage (ATES) based on the monitoring data from 73 Dutch ATES systems. With a total abstraction of 30.4 GWh heat and 31.8 GWh cold per year, the average annual amount of supplied thermal energy was measured as 932.8 MWh. The data analysis revealed only small thermal imbalances and small temperature losses during the storage period. The abstraction temperatures are around 10 and 15 ° C during summer and winter, respectively. However, the temperature difference between the abstraction and injection wells is 3–4 K smaller compared to the optimal design value. This indicates insufficient interaction between the energy system and the subsurface by an inadequate charging of the aquifer. In addition, the amount of stored and abstracted thermal energy is approximately 50% lower than the capacities licensed by the authorities. This results in an unsustainable utilization of the subsurface. Even though ATES technology proved its enormous potential to significantly reduce CO2 emissions, the operation still can be optimized. This applies in particular to an adequate planning and maintenance of the building energy system and a more efficient use of the available subsurface space. Highlights: Monitoring data of 73 Dutch ATES systems are analyzed. Mean abstraction temperatures are 10 °C (summer) and 15 °C (winter). Temperature losses during the storage period are between 1 and 2 K. Interaction between ATES and energy system has to be improved. ATES systems abstract < 50% of the licensed amount of energy.